Comparison of Three Different Fertigation Strategies for Drip Irrigated Table Grapes – Part II. Soil and Grapevine Nutrient Status - Howell, C.L.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
A field trial was carried out in a drip irrigated Dan-ben-Hannah/Ramsey table grape vineyard near Paarl in the Berg River Valley region of South Africa to compare three fertigation strategies. Fertilisers were applied (i) two weeks after bud break, fruit set and post-harvest (LF), (ii) weekly from two weeks after bud break until ten weeks after harvest, except during berry ripening (WF), and (iii) in daily fertigation pulses (DF). Grapevines of all treatments received c. 116 kg/ha N, 22 kg/ha P and 92 kg/ha K per season. Grapevines of all the fertigation strategies were thinned to obtain a normal and high crop load, which is 26 and 36 bunches per grapevine respectively for Dan-ben-Hannah under the given conditions. In the case of DF, the soil directly beneath the drippers became acidic after three years. Salt also accumulated on the perimeter of the wetted soil volumes. Petiole P of the DF grapevines was 77% higher than that of the LF and WF grapevines. Daily fertigated grapevines bearing normal crop loads had 20% to 30% higher leaf blade P than the LF or WF grapevines. Leaf blade K of the WF grapevines was lower than in the grapevines bearing a normal crop load of the LF and DF strategies. Grapevines bearing high crop loads tended to have lower juice N than grapevines with a normal crop load. Juice P of the DF grapevines was higher than that of the LF and WF grapevines, regardless of crop load. Daily pulse fertigation promoted the accumulation of N, P and K in the berry skins.